Evaluative study of platelet apheresis by haemonetics MCS+ and comparison with random donor platelets - Fauzi, Haslinda Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
Platelet concentrates (PCs) can be prepared by two methods, including apheresis and random donor platelets (RDP). To ensure good quality of PCs, standards have been set up by Transfusion Medicine Unit and according to these apheresis PCs should have platelet count more than 2. 0 x 10 I I I Unit, volume more than 40mL per 60 x I 09 platelets and white blood cell (WBC) contamination less than 0.5 x 1091 Unit. Similarly RDP should have platelet count more than 55 x 1091 Unit; volume within 40 to 60 mL, WBC contamination should be less than 0.5 x 109 I Unit and red blood cell (RBC) contamination should be less than 1.0 x 1091 Unit. For both platelet apheresis and RDP there should be no growth of microorganism. The main objective of this study was to determine whether the standards were met or not and to compare the different parameters including contamination with bacteria, WBC and RBC between RDP and apheresis. To meet our objectives we designed a prospective study to be conducted in Transfusion Medicine Unit and 47 apheresis PCs and 47 RDP samples were collected. We also studied the effects of apheresis on pre- and post-donation full blood count (FBC), hemolysis and side effects experienced by 50 donors using Haemonetics MCS+. Results of our study showed that the criteria for apheresis PCs and RDP were met except for RBC contamination in both techniques and volume in RDP, WBC and RBC contaminations in apheresis PCs were unexpectedly higher than in RDP, while bacterial contamination was lower in apheresis PCs. Comparison of pre- and post donation counts showed, significant decrease in platelet count while WBC, hemoglobin and hematocrit levels were significantly increased. In general no hemolysis was observed in apheresis donors by Haemonetics MCS+. Citrate toxicity was mild but it was the most common side effect during apheresis donation. We concluded that quality of apheresis PCs and RDP met the standards except for RBC contamination, volume of RDP and bacterial contamination. Platelet apheresis by Haemonetics MCS+ is a safe, reliable and effective method.